Pathological upgrading at radical prostatectomy for patients with Grade Group 1 prostate cancer: implications of confirmatory testing for patients considering active surveillance. (15th October 2018) - Kaye, Deborah R.; Qi, Ji; Morgan, Todd M.; Linsell, Susan; Ginsburg, Kevin B.; Lane, Brian R.; Montie, James E.; Cher, Michael L.; Miller, David C.
Abstract : Objective: To examine the association between National Comprehensive Cancer Network (NCCN) risk, number of positive biopsy cores, age, and early confirmatory test results on pathological upgrading at radical prostatectomy (RP), in order to better understand whether early confirmatory testing and better risk stratification are necessary for all men with Grade Group (GG) 1 cancers who are considering active surveillance (AS). Patients and Methods: We identified men in Michigan initially diagnosed with GG1 prostate cancer, from January 2012 to November 2017, who had a RP within 1 year of diagnosis. Our endpoints were: (i) ≥GG2 cancer at RP and (ii) adverse pathology (≥GG3 and/or ≥pT3a). We compared upgrading according to NCCN risk, number of positive biopsy cores, and age. Last, we examined if confirmatory test results were associated with upgrading or adverse pathology at RP. Results: Amongst 1966 patients with GG1 cancer at diagnosis, the rates of upgrading to ≥GG2 and adverse pathology were 40% and 59% ( P < 0.001), and 10% and 17% ( P = 0.003) for patients with very‐low‐ and low‐risk cancers, respectively. Upgrading by volume ranged from 49% to 67% for ≥GG2, and 16% to 23% for adverse pathology. Generally, more patients aged ≥70 vs <70 years had adverse pathology. Unreassuring confirmatory test results had a higher likelihood of adverse pathology than reassuring tests (35% vs 18%, P = 0.017). Conclusions: Upgrading and adverse pathology are common amongst patients initially diagnosed with GG1 prostate cancer. Early use of confirmatory testing may facilitate the identification of patients with more aggressive disease ensuring improved risk classification and safer selection of patients for AS.